The council of metropolitan see and its canonical basis: an orthodox approach = Synode métropolitain et ses fondements canoniques : Perspective orthodoxe = Sinodo metropolitano e le sue basi canoniche : Prospettiva ortodossa - Mititelu, Cătălina (Ecumeny and law, 2019)
In this canonical study, the reader of the article will have an opportunity to become acquainted with an old European canonical-juridical institution, that is, the synodality, and, ipso facto, about its juridical regime. And, naturally, the reader can get acquainted more closely with the provisions of the canonical norms of the Eastern Church regarding the eparchial (metropolitan) synodality institution, and, ipso facto, with the issue of the regime of the synodality. Since the canonical bases of the synodality regime are foreseen in the canonical legislation of the first millennium, we had to make an hermeneutical analysis of its text, which showed us that, by resorting to ad fontes, we can also pave the way that would go towards the restoration of the unity of the two Christian worlds, namely, Pars Orientis and Pars Occidentis.